2000
DOI: 10.1001/archopht.118.8.1076
|View full text |Cite
|
Sign up to set email alerts
|

Aging Affects the Retrobulbar Circulation Differently in Women and Men

Abstract: Background: While aging clearly has protean biological effects on every organ system, the differential effects of aging in women and men in the retrobulbar vasculature, to our knowledge, have never been investigated. Because glaucoma and age-related macular degeneration are closely linked to advanced age, we performed a crosssectional study using color Doppler imaging of 4 retrobulbar vessels in both healthy women and men. Objective: To define the influence of aging per se on ocular hemodynamics. Methods: Wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 27 publications
5
86
0
2
Order By: Relevance
“…It is possible that the differences between the two study groups in age, IOP, and visual field damage may justify the differences in blood flow parameters between POAG and PXE patients. However, Harris et al, 28 using CDI, found that in healthy subjects the ophthalmic arterial EDV decreased and RI rose with 29 found that in normal subjects the flow velocities of all considered vessels progressively decline whereas RI values increase with advancing age. Glaucomatous eyes with uncontrolled IOP and with visual field worsening showed a statistically significant decrease in the EDV flow velocities and an increase in the resistivity index value in ciliary arteries.…”
Section: Discussionmentioning
confidence: 98%
“…It is possible that the differences between the two study groups in age, IOP, and visual field damage may justify the differences in blood flow parameters between POAG and PXE patients. However, Harris et al, 28 using CDI, found that in healthy subjects the ophthalmic arterial EDV decreased and RI rose with 29 found that in normal subjects the flow velocities of all considered vessels progressively decline whereas RI values increase with advancing age. Glaucomatous eyes with uncontrolled IOP and with visual field worsening showed a statistically significant decrease in the EDV flow velocities and an increase in the resistivity index value in ciliary arteries.…”
Section: Discussionmentioning
confidence: 98%
“…The changes in retrobulbar arteries during menopause are not clear. Harris et al [35]compared postmenopausal women who had never received HRT with similarly aged men and found the women to have decreased EDV and increased RIs of the NSPCA and TSPCA. The same authors also found a decrease in EDV and an increase in the RI of the OA, a decrease in the blood flow velocity of the NSPCA and TSPCA in postmenopausal women compared with young menstruating women [34].…”
Section: Discussionmentioning
confidence: 99%
“…There is preliminary evidence that early menopause may be associated with increased risk for several major ocular diseases, including glaucoma, which may be linked to ocular ischemia [30, 31]. In previous studies the effects of menopause and HRT on retrobulbar blood flow were not well defined [32, 33, 34, 35]. In this study, the effects of menopause and HRT on tear quality and quantity, IOP and retrobulbar blood flow were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Harris et al (17) estudaram a circulação retrobulbar através do Doppler colorido de 125 voluntários sem alteração ocular, com idade entre 20 e 90 anos e encontraram aumento do índice de resistência da artéria ciliar curta posterior em pacientes do sexo feminino em relação à idade.…”
Section: Discussionunclassified